Synthesis, Spectroscopic Characterization and Theoretical Study of Schiff Bases Derived from Phenylsulfonylamide (Journal of Scientific Research, 2009)
The synthesis, characterization, and theoretical study of two Schiff bases of ligands derived from condensation of sulphoacetamide sodium with 4-methoxy benzaldehyde and salicalaldehyde arereported. Spectroscopic techniques, including IR, UV, 1H NMR, and CHN analysis were used to identify the product. The calculated HOMO is largely localized on the N-benzylideneaniline fragment, while the calculated LUMO of the studied molecule is seen to be substantially localized along the C–C axis of the conjugated system. Keyword: Sulphoacetamide sodium complex; Schiff bases; Sulpha drug; Semi-empirical (PM3) methods.  © 2009 JSR Publications. ISSN: 2070-0237 (Print); 2070-0245 (Online). All rights reserved.  DOI: 10.3329/jsr.v1i3.2589            J. Sci. Res. 1 (3), 563-568 (2009)